2009
DOI: 10.3390/medicina45100102
|View full text |Cite
|
Sign up to set email alerts
|

The influence of surgical treatment and red blood cell transfusion on changes in antioxidative and immune system parameters in colorectal cancer patients

Abstract: Summary. Objective. To determine the effect of surgical treatment and red blood cell transfusion on the parameters of antioxidative and immune systems in patients withMedicina (Kaunas) 2009; 45(10)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
3
6
0
1
Order By: Relevance
“…In our study, measuring serum MDA concentration in patients with various CRC stages we found the concentration of this oxidative stress marker to significantly increase to the third stage of the disease and as such persisted into the fourth stage of the disease. Similar results have been reported by Surinenaite et al , who found the concentration of MDA in serum of patients with CRC to be significantly higher in the third stage of the disease as compared to the second stage, and to have decreased significantly after surgical treatment when compared with the preoperative level ( 14 ).…”
Section: Discussionsupporting
confidence: 87%
“…In our study, measuring serum MDA concentration in patients with various CRC stages we found the concentration of this oxidative stress marker to significantly increase to the third stage of the disease and as such persisted into the fourth stage of the disease. Similar results have been reported by Surinenaite et al , who found the concentration of MDA in serum of patients with CRC to be significantly higher in the third stage of the disease as compared to the second stage, and to have decreased significantly after surgical treatment when compared with the preoperative level ( 14 ).…”
Section: Discussionsupporting
confidence: 87%
“…Mendonça et al ( 43 ) reported that higher MDA levels were found in the serum of patients with CRC at an advanced stage (III). Surinenaite et al ( 44 ) also reported that in 65 patients serum MDA level was more elevated in advanced than early stage CRC. The serum MDA level was significantly decreased after surgical treatments compared to pre-surgical status.…”
Section: Discussionmentioning
confidence: 92%
“…In patients with advanced inoperable CRC, serum MDA concentration is much higher than in those with primary CRC [35]. Surinenaite et al [36] also found that in 65 stage II/III CRC patients, serum MDA level was more elevated in stage III than stage II patients. The serum MDA level was significantly decreased after surgical treatments compared to presurgical status [36].…”
Section: Malondialdehyde the Most Mutagenic Product Of Lipid Peroxidmentioning
confidence: 88%
“…Surinenaite et al [36] also found that in 65 stage II/III CRC patients, serum MDA level was more elevated in stage III than stage II patients. The serum MDA level was significantly decreased after surgical treatments compared to presurgical status [36]. These observations suggest that MDA might relate to CRC carcinogenesis and progression.…”
Section: Malondialdehyde the Most Mutagenic Product Of Lipid Peroxidmentioning
confidence: 91%